Culture, ecology, and economy of fire management in North Australian Savannas : rekindling the Wurrk tradition - Russell-Smith, Jeremy; Whitehead, Peter J.; Cooke, Peter (CSIRO Pub., 2009)
This engaging volume explores the management of fire in one of the world's most flammable landscapes: Australia's tropical savannas, where on average 18% of the landscape is burned annually. Impacts have been particularly severe in the Arnhem Land Plateau, a centre of plant and animal diversity on Indigenous land. Culture, Ecology and Economy of Fire Management in North Australian Savannas documents a remarkable collaboration between Arnhem Land's traditional landowners and the scientific community to arrest a potentially catastrophic fire-driven decline in the natural and cultural assets of t.